Analysis of the Effectiveness of Rural and Urban Land and Building Tax Collection Based on E-SPPT PBB-P2 in Increasing Regional Tax Revenue in the Seribu Islands UPPD in 2021 - Purwatomo, Purwatomo; Irwansyah, Iwan; Harjo, Dwikora (Jurnal Manajemen Bisnis, Akuntansi dan Keuangan, 2024)
The effectiveness of P2 PBB collection in increasing tax revenue at the DKI Jakarta Thousand Islands UPPPD in 2021 based on the analysis of the primary and secondary data above shows that the aspect of achieving goals is assessed as not being effective, partly because it is seen from the dimension of effectiveness in the aspect of achieving targets which refers to the parameter Effectiveness shows in the five- year period 2019 - 2021 the performance is still not optimal, the PBB- P2 revenue target has never been achieved, In 2020, the PBB P2 tax revenue experienced a significant 33% decrease in comparison to the previous year, particularly. the main cause of which was due to the covid19 pandemic factor, as well as tax arrears (PBB P2) are also still large in number, and taxpayer compliance is still not optimal in paying taxes as seen from the fact that many SPPT PBB P2 have been issued but have not been paid.